Kajian Konsep Fisika Kinematika Gerak pada Hero Khufra (Skill Tyrent’s Revenge) dalam Game Online Mobile Legends Bang Bang - Agus Anwar; Munir, Rahmawati; Inu Natalisanto, Adrianus; Djayus; Rayzy Perwitasari Sutaji Putri, Devina (JFT : Jurnal Fisika dan Terapannya, 2024)
In the Mobile Legends Bang Bang game, one aspect related to motion kinematics is the charging time for the hero Khufra, which influences the distance of displacement from the starting point to the endpoint. As a result, it is necessary to study the concept of kinematic motion in this game, particularly focusing on the use of Khufra's Tyrent's Revenge skill. This study aims to explore the concept of motion kinematics in Mobile Legends Bang Bang and examine how the charging duration of Khufra's Tyrent’s Revenge skill affects the displacement distance. The research utilizes data in the form of video recordings showcasing the use of Tyrent’s Revenge by Khufra in the game. The videos are analyzed using video tracking software that can generate visualization of graphs, time, and distance of movement. The data obtained is then entered into Excel software to determine the linear regression curve and calculate the R-Squared (R^2) value. The results of this research show that in the game Mobile Legends Bang Bang, the kinematics of motion can be described through the displacement distance of the Khufra’s hero from the starting point to the end point. The analysis results indicate a linear regression curve with the equation y = 0.4422x - 1.0723 and an R² value of 0.9757. A value of R2 approaching 1 indicates a strong influence of launch time on the displacement distance of Khufra’s hero.